Optimization of Friction Stir Welding Parameters of AA5052-H32 Aluminium Alloy using Taguchi and Taguchi-Pareto Methods - Adetayo Moses Bamidele; Sunday Ayoola Oke; John Rajan; Babatunde Alade Sawyerr; Ebun Fasina; Kasali Aderinmoye Adedeji; Elkanah Olaosebikan Oyetunji (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2023)
It is difficult to improve the quality of friction stir welded joints of AA5052-H32 material because of scarce metrics on its concurrent optimization and prioritization. However, the objective of this article is to obtain optimal parametric values and identify important parameters using the Taguchi-Pareto method during the friction stir welding process of AA5052-H32 material. Then the ranks, delta values and optimal parameters are determined. The critical parameters identified for the friction stir welding process are the tool pin, rotational speed, welding speed and tool angle. When comparing the results of these parameters using the Taguchi method and Taguchi-Pareto method, the rotational speed retained its first position in both methods; the tool tilt angle gained the second position in the Taguchi-Pareto method from its third position when only the Taguchi method was considered. The welding speed became the third position in the Taguchi-Pareto method against the second position that it had in the Taguchi method. However, the tool pin profile retained its last position in both methods. Consequently, the rotational speed is the best parameter while the tool pin profile is the worst parameter. For the Taguchi-Pareto method, the optimal parametric setting is TPP2/TPP4RS1WS4TTA3. This is interpreted as cylindrical tapered or square tapered for the tool profile, 40 rpm of rotational speed, 75 mm/min of welding speed and 1.5° of tool tilt angle. The novelty of this study is the scope of analysis of the AA5052-H32 material that extends beyond the Taguchi method to the Taguchi-Pareto method where the concurrent optimization and prioritization of friction welding parameters are achieved.